THE ROLE OF THE EMOTIONAL FACTOR IN THE EDUCATIONAL AND COGNITIVE ACTIVITY OF FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2011)
The article explains the role of emotional factors in educational-cognitive activity of students - future teachers. Reveals the "emonational core" of the structural components of the educational-cognitive activity: substantive, procedural and motivational, whici function in a coherent system.
Keywords: emotions; intellectual sense, knowledge; educational-cognitive activity; the preparation of future teacgers